Pengaruh Komunikasi, Lingkungan Kerja Fisik Dan Disiplin Kerja Karyawan Terhadap Produktivitas Karyawan Pada Pt Pembangunan Daerah Bali Kantor Pusat - Arisanthi, Ni Kadek Desy; Netra, I Gusti Salit Ketut (E-Jurnal Manajemen; Vol 2 No 11 (2013), 2013)
This study aimed to determine the effect of simultaneous or partial significantly between communication, physical work environment, and work discipline on employee productivity at PT. Bank Pembangunan Daerah Bali Kantor Pusat. Population at PT. Bank Pembangunan Daerah Bali Kantor Pusat as much as 221 people. Sampling was done by using the propotionate Probability Sampling Stratified Random Sampling. The large number of samples is 69. Analysis of the data used is multiple linear regression. The test results simultaneously or partially indicate that communication (X1), the physical work environment (X2), work discipline (X3) on work productivity (Y). Large effect was 63.1%. Variable labor discipline is the most dominant variables affecting employee productivity at PT. Bank Pembangunan Daerah Bali Kantor Pusat . Keyword:        communication, physical work environment, work discipline, employee productivity.